Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Konsumen pada Sabana Fried Chicken Jatimakmur Bekasi - Muhammad Khafi; Isnurrini Hidayat Susilowati (MAMEN: Jurnal Manajemen, 2023)
the effect of price and service quality on customer satisfaction at Sabana Fried Chicken Jatimakmur Bekasi, the method used in this study is a quantitative method and data collection techniques for documentation studies, in addition to data processing using the SPSS application. The instrument used to collect data is a questionnaire. This research was conducted by direct research to Sabana Fried Chicken outlets Jatimakmur in April – May 2023. Respondents in the study were Sabana Fried Chicken Jatimakmur Bekasi consumers, totaling 90 people. And distributing questionnaires with each variable, namely variable X1 price, X2 service quality, and Y consumer satisfaction. Quantitative analysis consists of testing the instrument (validity and reliability of the instrument). Multiple regression analysis, classical assumption test, t test (Persial) and f test (simultaneous) The results of this study are in line with those conducted by Natasha Hosang, 2019. It can be said that the price and service quality variables simultaneously (simultaneously) have a significant effect on Variable Consumer Satisfaction at Sabana Fried Chicken Jatimakmur Bekasi.